Perlindungan Konsumen Muslim terhadap Produk Pangan Daging Non Kemasan melalui Jaminan Produk Halal - Intan Nurani; Moh Zakky; Efridani Lubis (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2021)
Related to the validity of non-packaged meat food products, Law No. 8 of 1999 on Consumer Protection only stipulates that business actors are prohibited from producing and/or trading goods and/or services that do not follow the provisions of halal production, as stated